Amyloid‐β removal from the brain is blocked by circulating amyloid‐forming amylin secreted by the pancreas. (December 2021) - Ly, Han; Verma, Nirmal; Kotiya, Deepak; Goldstein, Larry B; Jicha, Gregory A; Despa, Florin
Abstract: Background: Increasing amyloid‐β (Aβ) transport from the brain provides a novel therapeutic approach for Alzheimer's disease (AD). Our team recently showed: 1, the brain microvasculature accumulates amylin, an amyloid‐forming hormone secreted from the pancreas, in both familial and sporadic forms of AD; 2, amylin and Aβ often co‐localize in the brain parenchyma and microvasculature; 3, cerebrovascular amylin deposition is associated with behavioral deficits in rats, independent of Aβ pathology; and 4, pancreatic expression of human amylin in APPswe/PS1dE9 (APP/PS1) rats accelerates the development of AD‐like pathology. We tested the hypothesis that the removal of Aβ from the brain is in part affected by amylin deposition in the brain microvasculature. Method: Amylin levels were measured in blood from 38 cognitively impaired and 41 cognitively unimpaired individuals. Evidence of amylin‐Aβ co‐localization was assessed in brain slices from 56 persons with AD and 37 cognitively unaffected individuals. To explore the potential mechanisms by which amylin might affect Aβ transport, we genetically manipulated amylin secretion in APP/PS1 and non‐APP/PS1 rats. Result: Average blood amylin levels were higher in those with dementia (DEM) or mild cognitive impairment (MCI) compared to those who were cognitively unimpaired (CU) (8.0 ± 2.2 pM vs. 4.7 ± 1.4 pM vs. 2.8 ± 0.5 pM; one‐way ANOVA, P < 0.0001). In human AD brains and brains of APP/PS1 rats with pancreatic expression of amyloid‐forming human amylin, Aβ accumulation within the perivascular space frequently co‐localized with amylin deposits. In non‐APP/PS1 rats expressing human amylin, amylin accumulated in brain capillaries which induced downregulation of the low‐density lipoprotein receptor‐related protein 1 (LRP1), the Aβ transport protein, and was associated with a lower plasma‐to‐brain Aβ ratio compared to wild type littermates (0.52 ± 0.01 vs . 0.64 ± 0.02, P = 0.0021). Conclusion: Systemic amylin dyshomeostasis leads to amylin accumulation in small cerebral vessels causing cerebral microvascular dysfunction and interference with vascular routes for Aβ removal from the brain. Lowering the blood amylin level in early AD could improve Aβ clearance from the brain.